Mutant Allele-Specific Uncoupling of PENETRATION3 Functions Reveals Engagement of the ATP-Binding Cassette Transporter in Distinct Tryptophan Metabolic Pathways . Issue 3 (28th May 2015) - Lu, Xunli; Dittgen, Jan; Piślewska-Bednarek, Mariola; Molina, Antonio; Schneider, Bernd; Svato¡, Ale¡; Doubský, Jan; Schneeberger, Korbinian; Weigel, Detlef; Bednarek, Paweł; Schulze-Lefert, Paul
Abstract : A specific mutation in the gene encoding Arabidopsis PEN3 ATP-binding cassette transporter indicates diverse tryptophan metabolites as PEN3 substrates. Abstract: Arabidopsis ( Arabidopsis thaliana ) PENETRATION ( PEN ) genes quantitatively contribute to the execution of different forms of plant immunity upon challenge with diverse leaf pathogens. PEN3 encodes a plasma membrane-resident pleiotropic drug resistance-type ATP-binding cassette transporter and is thought to act in a pathogen-inducible and PEN2 myrosinase-dependent metabolic pathway in extracellular defense. This metabolic pathway directs the intracellular biosynthesis and activation of tryptophan-derived indole glucosinolates for subsequent PEN3-mediated efflux across the plasma membrane at pathogen contact sites. However, PEN3 also functions in abiotic stress responses to cadmium and indole-3-butyric acid (IBA )-mediated auxin homeostasis in roots, raising the possibility that PEN3 exports multiple functionally unrelated substrates. Here, we describe the isolation of a pen3 allele, designated pen3-5, that encodes a dysfunctional protein that accumulates in planta like wild-type PEN3. The specific mutation in pen3-5 uncouples PEN3 functions in IBA -stimulated root growth modulation, callose deposition induced with a conserved peptide epitope of bacterial flagellin (flg22), and pathogen-inducible salicylic acid accumulation from PEN3 activity in extracellular defense, indicating the engagement of multiple PEN3 substrates in different PEN3-dependent biological processes. We identified 4- O -β-d -glucosyl-indol-3-yl formamide (4OGlcI3F ) as a pathogen-inducible, tryptophan-derived compound that overaccumulates in pen3 leaf tissue and has biosynthesis that is dependent on an intact PEN2 metabolic pathway. We propose that a precursor of 4OGlcI3F is the PEN3 substrate in extracellular pathogen defense. These precursors, the shared indole core present in IBA and 4OGlcI3F, and allele-specific uncoupling of a subset of PEN3 functions suggest that PEN3 transports distinct indole-type metabolites in distinct biological processes.